Electrospun acid-neutralizing fibers for the amelioration of inflammatory response. (1st October 2019) - Shen, Yanbing; Tu, Tian; Yi, Bingcheng; Wang, Xianliu; Tang, Han; Liu, Wei; Zhang, Yanzhong
Graphical abstract: Abstract: Biodegradable aliphatic polyesters, especially polylactide (PLA), polyglycolide (PGA), and their copolymer poly(lactide- co -glycolide) (PLGA), are the most representative and widely used synthetic polymers in the field of tissue engineering and regenerative medicine. However, these polyesters often give rise to aseptic inflammation because of their acidic degradation products after implantation. Here, unidirectional shell-core structured fibers of chitosan/poly(lactide- co -glycolide) (i.e., CTS/PLGA) with acid-neutralizing capability were developed for addressing the noted issue by coating the PLGA fiber surfaces with a layer of the alkaline chitosan by coaxial electrospinning. Our results showed that during a period of 8-week degradation, the shell-layer of chitosan with its unique alkaline nature for acid-neutralization obviously hindered the pH decrease as a result of the degradation of PLGA-core. In a mocked acidic environment testing of the human dermal fibroblasts, chitosan-enabled acidity neutralization could significantly reduce in vitro the secretion of inflammatory factors and downregulate the expression of related inflammatory genes. Thereafter, biocompatibility assessment in vitro showed that the CTS/PLGA fibers had poorer cell adhesion capacity than the PLGA fibers but were cytocompatible and promoted cell migration and secretion of collagen. Moreover, subcutaneous embedding for two and four weeks in vivo revealed that the CTS/PLGA fibers significantly reduced the recruitment of inflammatory cells and the formation of foreign body giant cells (FBGCs). This study thereby demonstrated the evident acid-neutralizing effect of the chitosan-coating layer on alleviating the inflammatory responses caused by the acidic degradation products of the PLGA-core. Our highly aligned CTS/PLGA fibers, as a kind of quasi "pH-neutral fibers" with the acid-neutralizing capability, could be potentially applied for engineering those architecturally anisotropic tissues (e.g., tendon/ligament) toward improved efficacy of regeneration. Statement of Significance: It is well known that acidic degradation products from representative aliphatic polyesters (e.g., PLA, PGA, and PLGA) give rise to the problem of aseptic inflammation. Various alkaline components acting as neutralizing agents have been used to address the noted issue. However, rather less attention has been paid to engineer these polyesters into a fibrous form with acid-neutralizing functionality. The present study proposes the concept of "pH-neutral fibers" and develops shell-core structured unidirectional fibers of chitosan/poly(lactide- co -glycolide) with acid-neutralizing capability for ameliorating inflammatory responses caused by the acidic degradation products of PLGA. It provides a comprehensive study encompassing fiber characterization and in vitro and in vivo evaluation, which would pave the way for developing sophisticated pH-neutral fibers for functional tissue regeneration.